Conformal orbit sparing radiation therapy: a treatment option for advanced skin cancer of the parotid and ear region. Issue 3 (19th March 2016) - Foley, Heath; Hopley, Shane; Brown, Elizabeth; Bernard, Anne; Foote, Matthew
Abstract: Introduction: New surgical methods have enabled resection of previously in‐operable tumours in the region of the parotid gland and ear. This has translated to deeper target volumes being treated with adjuvant radiotherapy. Due to the limitations of existing conformal techniques, alternative planning approaches are required to cover the target volume with appropriate sparing of adjacent critical structures. Although intensity modulated radiation therapy (IMRT) may be able to achieve these goals compared with the existing conformal method, a new orbital sparing radiation therapy (OSRaT) technique was evaluated as an alternative conformal planning process. The study objective was to evaluate the dosimetry of three planning methods: pre‐existing conformal, IMRT and OSRaT techniques. Methods: Ten patients were planned retrospectively using the existing three‐dimensional conformal radiotherapy (3DCRT), IMRT and OSRaT techniques. Dosimetry was analysed using the homogeneity index (HI), conformity index (CI), the volume of planning target volumes (PTV) under and over treated by the 95% isodose and dose to critical structures. Results: OSRaT achieved superior 95% coverage of the high‐dose PTV while delivering HI similar to IMRT for intermediate and high‐dose PTVs. The CI for the high‐dose PTV was comparable between the three techniques, however IMRT was statistically better for the low‐ and intermediate dose PTVs. All three techniques showed adequate orbital sparing, however OSRaT and IMRT achieved this with less under dosing of the PTVs. Conclusion: For the treatment of patients with advanced skin cancer of the parotid and ear, both IMRT and the OSRaT techniques are viable options. Abstract : A dosimetric comparison of three different radiation therapy (RT) delivery techniques to treat advanced skin cancer of the parotid and ear region was the objective of the study. All three techniques showed adequate orbital sparing, however orbital sparing RT (OSRaT) and intensity modulated radiation therapy (IMRT) techniques achieved this with less under dosing of the planning target volumes. For the treatment of patients with advanced skin cancer of the parotid and ear, both IMRT and the OSRaT techniques are viable options.